EVALUATION OF THE TEACHING PROCESSES AT SCIENCE HIGH SCHOOLS BASED ON A CONSTRUCTIVIST APPROACH. A SCALE DEVELOPMENT STUDY - Aslan, D.; Aydin, H. (SCIBULCOM LTD, 2015)
In this study, the evaluation of the teaching processes at the science high schools at which teachers employ a constructivist approach was made. A quantitative method was employed for the study. The internal consistency coefficient of the scale developed by the researchers is quite high. The Cronbach alpha values vary between alpha = 0.95 (1. factor 1) and alpha = 75 (4. factor). On the other hand, for the sum of scale, the alpha value was calculated as alpha = 0.96. The universe of the study consists of teachers at six science high schools in Turkey from public and private sectors and the sample of the study consists of teachers from private and public science high schools in Istanbul. On the scale of teachers, the number of items are 45. For the result of this pilot study, the teacher scale was determined as 24 items. The exploratory factor analysis of the scale was analysed and four factors have emerged regarding the size of the teacher scale.
Keywords: constructivist approach; teaching process; evaluation; quantitative method; Chemistry